Investasi Saham Syariah Berbasis Maqashid: Studi pada Indeks Saham Syariah Indonesia - Saputri, Diyah; Astuti, Yuni (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2025)
Maqasid Syariah allows us to apply the principles of Maqasid in investing, including investing in stocks. Stock indices have screening criteria that can be adjusted to comply with existing Maqasid Syariah principles. This research aimed to analyze how the ISSI, IDX ESG Leaders, IDX High Dividend, and IDX Sharia Growth stock indices can be utilized for investment in accordance with the five principles of maqashid shariah. This quantitative descriptive research used secondary data from financial report and IDX. The collected data then filtered using the Maqashid Sharia principles appropriate to each stock index. The stock then valued using the PER approach. The analysis results indicate that TLKM and UNVR stocks meet the criteria of the five maqashid shariah principles. Subsequently, these two stocks were evaluated using the Price to Earnings Ratio (PER) approach. The data used consists of Earnings Per Share (EPS) over the past eleven years and the annual average PER. The results reveal that TLKM is currently undervalued, whereas UNVR is overvalued. This study further demonstrates that investors can leverage these stock indices to invest in alignment with the five principles of maqashid shariah.